Metode Penyimpanan Bakteri Vibrio alginolitycus dan Vibrio harveyi Dalam Media TSB (Tryptic Soy Broth) Dan Gliserol - Huyyirnah Huyyirnah; Fitriyani Fitriyani (Integrated Lab Journal, 2020)
Various kinds of studies or research conducted at the Marine Microbiology Laboratory of the Faculty of Marine and Fisheries Sciences, Hasanuddin University mostly use microbial isolates as test materials. Therefore, it is necessary to collect, store and maintain microbes properly. Important bacteria that are often used are Vibrio alginolyticus and Vibrio harveyi. Both of these bacteria require good handling and proper preservation so that their viability is maintained. So it is important to do research to find the right method of storing V. alginolyticus and V. harveyi bacteria in TSB (Tryptic Soy Broth) and glycerol medium. The method used in this research is an experimental method using 2 types of bacteria and 4 levels of treatment, each treatment with 3 replications. The treatments consisted of TSB + glycerol 10%, 15%, 20%, 25% stored at -20ºC for 56 days. The results showed that V. harveyi was effective and had the highest growth power during storage in TSB media with 10% glycerol at -20 ° C, while V. alginolyticus on TSB media with glycerol 10% -15% at -20 ° C. The effective storage time for V.harveyi and V. alginolyticus bacteria is on day 14 to day 28.